The Effect of Digitalization on Non Performing Loan and Fee Based Income in Banking - Alkahfi, Muhammad Zaid; Prasetyo, Tri Joko; Sudrajat, Sudrajat (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates the influence of mobile banking transactions, technology, and information investment on non performing loan and fee-based income. This study was conducted on commercial banks listed on the Indonesia Stock Exchange during 2018-2022. The purposive sampling method was used to select the sample, and the data came from the bank's annual report. Multiple regression analysis is used to analyze the relationship between variables. Partial test results show that mobile banking transactions have a significant adverse effect on the NPL ratio and a significant positive effect on fee-based income. Meanwhile, technology and information investment does not affect the NPL ratio but significantly positively affects fee-based income. These results show that increasing mobile banking transactions can support non performing loan and fee-based income.